Advanced techniques in logic synthesis, optimizations and applications (New York : Springer, 2011)
This book covers recent advances in the field of logic synthesis and design, including Boolean Matching, Logic Decomposition, Boolean satisfiability, Advanced Synthesis Techniques and Applications of Logic Design. All of these topics are valuable to CAD engineers working in Logic Design, Logic Optimization, and Verification. Engineers seeking opportunities for optimizing VLSI integrated circuits will find this book as an invaluable reference, since there is no existing book that covers this material in a systematic fashion.
La función de los autores fue determinada por el catalogador